Medical Device Materials IV : Proceedings of the Materials & Processes for Medical Devices Conference 2007, September 23-27, 2007, Palm Desert, California, USA - Gilbert, Jeremy (ASM International, 2008)
Proceedings from the only conference on medical devices that brings together scientists and product, research, design and development engineers from around the globe to present the latest developments in materials, processes, product performance and new technologies for medical/dental devices. --